THE CORRELATION OF PARENTAL ROLE TOWARDS HIGH SCHOOL STUDENTS’ DEMORALIZATION IN INDONESIA - I GUSTI NGURAH OCTAVA SEVENTILOFA (SOSIAL SAINS DAN TEKNOLOGI, 2023)
This study explores the connection between parental roles and student demoralization in Indonesian high schools. Grounded in Bronfenbrenner's Ecological Systems Theory and the Self-Determination Theory, the research investigates the impact of parental support on students' psychological well-being. Findings highlight the crucial role of parental involvement in preventing demoralization, emphasizing the need for supportive family environments. Cultural dynamics, shaped by collectivism, influence the multifaceted parent-student relationship. Empirical insights reveal complex interplays of financial incentives, teacher motivation, and parental engagement. The study underscores the broader implications for educational policies, emphasizing the importance of effective communication between parents and institutions. Recognizing cultural nuances, this research contributes to understanding and mitigating student demoralization in the Indonesian educational landscape